Model Platform Sharing Economy di Indonesia Studi Kasus: Unicorn Lokal - Prayogi Restia Saputra; Nur Hayatin (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
The sharing economy platform is a concept that is not yet stable and will continue to grow. This is evidenced by the various types of sharing economy platforms developed, especially in Indonesia. Many applications are made, but there are only a few applications that succeed in their business even reaching the Unicorn. They are Gojek, Traveloka, Tokopedia and Bukalapak. This study answers the question of how a typology of economic models sharing platforms in Indonesia is successful by taking the four unicorns as objects. The basic model of sharing economy used consists of four models taking into account the level of company control over participants and the level of competition between participants. Typology was developed through analysis of qualitative data obtained by observing the 4 Unicorn application which became the most successful platform in terms of user acquisition, active users, and transaction volumes. The theoretical contribution of this research is the sharing economic categorization model in Indonesia, considering that there is no research that presents the generic typology as intended. While the practical contribution is to provide a reference for beginners and investors about sharing economic models that are relevant for the Indonesian market. From the results of this study, we will know the typology model of a sharing economic platform that is developing in Indonesia, so it is expected to be a reference for business development towards the industrial revolution era 4.0.